Pencil‐Drawn Dual Electrode Detectors to Discriminate Between Analytes Comigrating on Paper‐Based Fluidic Devices but Undergoing Electrochemical Processes with Different Reversibility. Issue 11 (2nd October 2013) - Dossi, Nicolò; Toniolo, Rosanna; Piccin, Evandro; Susmel, Sabina; Pizzariello, Andrea; Bontempelli, Gino
Abstract A simple method is described to discriminate between analytes comigrating under on‐plate separation conditions, whose electrochemical behavior displays different reversible characters. It is based on the use of dual electrode detectors pencil‐drawn at the end of paper‐based fluidic channels defined by hydrophobic barriers. Simultaneous detection of comigrating species is achieved by applying to the upstream pencil‐drawn working electrode a potential for the oxidation (or reduction) of both analytes, while to the downstream pencil‐drawn working electrode a potential is imposed for the reverse process involving the product of the sole analyte undergoing a reversible enough electrochemical process. The performance of these inexpensive devices was preliminarily optimized by adopting hexacyanoferrate(II) as prototype species undergoing a reversible anodic process at carbon electrodes. They were then used as dual electrode detectors for thin‐layer chromatographic runs conducted on paper‐based microfluidic devices. Two types of synthetic solutions, one containing different contents of dopamine (DA) and ascorbic acid (AA) and the other of paracetamol (PA) and AA, were chosen as model samples. This choice was prompted us by the fact that in both cases these analytes comigrated under the adopted experimental conditions and required similar enough oxidation potentials. Nevertheless, DA and PA underwent reversible enough anodic processes while an irreversible electrochemical reaction is involved in the AA oxidation. Satisfactory results were found for both couples of target analytes, whose simultaneous detection was achieved within 230 s and was characterized by good enough repeatability and sensitivity. In particular, this approach appears to be well suited for the rapid and inexpensive assembling of electrochemical detectors for flow analysis systems.